Prevalence, predictors and challenges of gestational diabetes mellitus screening among pregnant women in northern Tanzania. Issue 2 (13th December 2017) - Njete, H. I.; John, B.; Mlay, P.; Mahande, M. J.; Msuya, S. E.
Abstract: Objectives: To determine the prevalence and predictors of gestational diabetes mellitus (GDM) as well as acceptability of returning for glucose tolerance testing among pregnant women in Moshi municipality, northern Tanzania. Methods: Cross‐sectional study from October 2015 to April 2016 among women with gestation age of 24–28 weeks of pregnancy attending at Kilimanjaro Christian Medical Centre (KCMC) referral hospital, Majengo and Pasua Health Centres. Women were interviewed and requested to return the next day (window within a month, depending on gestational age) for fasting plasma glucose (FPG) testing, followed immediately by a 75 g oral glucose tolerance test (OGTT). GDM was diagnosed using the 2013 WHO criteria. Logistic regression was conducted to reveal independent predictors for GDM. Results: Of 433 interviewed women, 100 (23%) did not return for FPG and OGTT testing. The prevalence of GDM among the 333 screened women was 19.5%, and 3% had diabetes in pregnancy (DIP). GDM was significantly associated with age ≥35 years (adjusted OR 6.75), pre‐pregnancy obesity (AOR 2.22) and history of abortion (AOR 2.36). Conclusion: Prevalence of GDM is high in Moshi. We recommend introduction of routine screening for hyperglycaemia during pregnancy along with strategies for follow‐up to prevent long‐term effects of GDM and DIP in women and their children.